A Conceptual Tree Model Explaining Legacy Effects on Stem Growth - Zweifel, Roman; Sterck, Frank (Frontiers in Forests and Global Change, 2018)
Tree species largely differ in the amount of annual stem growth explained by current-year conditions. Historic conditions have been shown to additionally explain a significant fraction of the unexplained variance. So far there is no mechanism described explaining why species differ in such legacy effects, obscuring our understanding of species differences in annual stem growth responses to climate. We present a generic conceptual view on key processes determining stem growth. We link current and historic conditions and their impacts on growth by considering the lifetime of functional organs and reserves as a way to quantify legacy effects. We propose how tree species with long organ lifetimes are determined by longer periods of historic conditions than species with short organ lifetimes, and why these species differ in their responses to current conditions. We investigated the hypothesis that including lifetime as variable in a process-based tree model allows for explaining different growth responses to current-year conditions. We show that species with short organ and reserve lifetimes are more sensitive to - and better track - current environmental conditions and therefore respond more strongly to current conditions than species with long lifetimes. Instead, the species with longer organ lifetimes respond more strongly to historic conditions and thus buffer their growth responses to current conditions. We propose the impact of historic environmental conditions being controlled by organ and reserve lifetimes and partially explaining the strength of legacy effects and the explanatory power of current-year environmental conditions on stem growth of different species.